THE EFFECT OF LEARNING MODELS ON MATHEMATICS LEARNING OUTCOMES ASSESSED FROM THE ACTIVITY OF VIII - Wiwin Fajriah Hanna; Uswatun Khasanah (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2020)
This study aims to determine whether or not there is a significant influence (1) the learning model on the mathematics learning outcomes of VIII grade students of SMP Muhammadiyah 3 Yogyakarta Even Semester of 2019/2020 Academic Year, (2) the activity factor on the learning outcomes ofÂ  VIII grade students of SMP Muhammadiyah 3 Yogyakarta Even Semester of 2019/2020 Academic Year, (3) the interaction between the learning model and the activeness of students on the mathematics learning outcomes of VIII grade students of Junior High School (SMP) Muhammadiyah 3 Yogyakarta Even Semester of the 2019/2020 Academic Year. This study's population was VIII grade students of SMP Muhammadiyah 3 Yogyakarta, consisting of 8 classes. A sample of 2 classes with 61 students was taken by random sampling technique, obtained VIII E as the experimental class and VIII F as the control class. Observation and tests are used as techniques in collecting the data. The research instrument was a test of mathematics learning outcomes and observations of student activeness. The data analysis technique used includes the prerequisite test and hypothesis testing. The results of the study with a significant level of 5% with dk: and indicate, (1) there is an effect of the learning model on mathematics learning outcomes, obtained = 44,390 dan = = 4,009, then it is obtained (2) there is an influence of student activeness factors on mathematics learning outcomes, obtained = 39,661 and = = 4,009, it is obtained , (3) there is a significant influence of the interaction between learning models and student activeness on mathematics learning outcomes, obtained = 14,731 and = = 4,009, then it is obtained.